Direct, indirect and total bilirubin and risk of incident coronary heart disease in the Dongfeng-Tongji cohort. (2nd January 2018) - Lai, Xuefeng; Fang, Qin; Yang, Liangle; Chen, Xuguang; Wang, Hao; Ma, Lin; Guo, Wenting; Liu, Miao; Yang, Handong; Zhang, Ce; Li, Xiulou; Min, Xinwen; et al.
Abstract: Background: Total bilirubin (TBIL) is known to be inversely associated with coronary heart disease (CHD) risk, however, whether this association is dose-response remains inconsistent and it is unclear which subtype of bilirubin is responsible for the potential protective effect. Methods: We included 12, 097 participants who were free of CHD, stroke, cancer and potential liver, biliary and renal diseases at baseline from September 2008 to June 2010 and were followed-up until October 2013. Cox proportional hazards models were used to assess the hazard ratios (HR) and 95% confidence interval (95% CI) of bilirubin with incident CHD risk. Results: The adjusted HRs for incident CHD increased with increasing direct bilirubin (DBIL) ( p for trend = .013). Participants within the highest quintile of DBIL had 30% higher risk of incident CHD compared to those in the lowest quintile (95% CI: 1.07, 1.58). In contrast, compared with subjects in the lowest quintile of TBIL, those in the third quintile had the lowest of 24% risk for CHD incidence (95% CI: 0.63, 0.92), which showed a U-shaped association ( p for quadratic trend = .040). Conclusions: DBIL was associated with a dose-response increased risk for CHD incidence. However, a U-shaped association existed between TBIL, indirect bilirubin and incident CHD risk. Key messages: Direct bilirubin is independently associated with incident coronary heart disease (CHD) in a dose-response manner. A similarly consistent U-shaped association was found between total bilirubin, indirect bilirubin and incident CHD. The potential protective effect of total bilirubin within the normal range on incident CHD should be mainly attributed to mild-to moderate elevated levels of indirect bilirubin.